WALKABILITY STUDY OF PEDESTRIAN WAYS USING URBAN NETWORK ANALYSIS (UNA) IN BLOK M AND ASEAN MRT STATION - Umni Afiya, Ishma
TOD Blok M-Sisingamangaraja (ASEAN) area is a Phase I transit area development that integrates the Jakarta MRT, TransJakarta BRT, Blok M Bus Station, and commuter line trains, located approximately 1.5 km from Kebayoran Lama Station. The development of transit-oriented areas aims to create a compact, high-density environment. The TOD Blok M-ASEAN area, situated in the center of the Kebayoran Baru cultural heritage area, presents a challenge for transit area development due to its inherently contradictory nature. Additionally, the development of a walkable transit area requires high connectivity and accessibility, particularly in the core zone. Currently, connectivity and accessibility are hindered by large private blocks surrounding the MRT station. To evaluate the quality of the urban environment—encompassing pedestrian paths, intensity, building mass layout, functions, and activities—this study aims to propose a development concept supported by quantitative analysis using Urban Network Analysis (UNA). The centrality analysis method within UNA is employed to analyze travel distance, accessibility, and interaction between spaces and people within a spatial network, thereby assessing the efficiency, accessibility, and connectivity of pedestrian infrastructure. There are five centrality impact analysis tools: reach index, gravity index, betweenness index, straightness index, and closeness index. These tools will be used to evaluate both the existing environment (UNA I simulation) and the preliminary design (UNA II simulation) as outlined in the TOD Block M-ASEAN Area City Design Guidelines (PRK) document, identifying the potential and issues within the area network. UNA III simulation will evaluate the results of the proposed development concept through iterative processes. The proposed development concept is based on key city design elements, including land use, building intensity and mass, pedestrian link systems, open space, and preservation. For effective transit area development, high reach index and straightness index results are beneficial, but adjustments must be made to accommodate cultural heritage considerations.